Has secondary science education become an elite product in emerging nations?- A perspective of sustainable education in the era of MDGs and SDGs - Alam, Gazi Mahabubul (Multidisciplinary Digital Publishing Institute, 2023)
Education is considered the single most important tool that supports the achievement of a nation’s sustainable development. However, if a particular education program itself deprives students with a lower socioeconomic status (SES) to access it and subsequently restricts them from achieving a better performance, should such an education program be labelled as sustainable education, supporting the achievement of the SDGs (Sustainable Development Goals)? This question remains to be answered. Science education, which is also treated as an “international product”, is the most essential component in education required to ensure sustainable national development. Consequently, science education should be a “right-based education program” that every “capable student”, regardless of his/her SES, is able to obtain. This motive should ideally ensure the best practice mode of sustainable development in education. Keeping this view in mind, this research was conducted in an emerging nation, namely Bangladesh, to examine whether secondary science education has become an elite product and its consequential effect on sustainable education. A qualitative research method that adopts a descriptive analysis of secondary data was primarily used. The secondary data were collected from the public archive(s). Findings suggest that, mostly, students with a privileged SES can access science education programs. Moreover, these students perform well in major public examination(s). Primary data further collected by Focus Group Discussions (FGDs) summarise that science education is an international product. The following artificial perception has thus developed. To participate in such a program, a significant informal budget from parents’ pockets is required in order to perform well. This is an obvious conflict with the spirit of sustainable education and SDGs. Hence, policy reform guidelines for decent practice are provided to resolve this misleading perception.